2018
DOI: 10.1002/jaba.528
|View full text |Cite
|
Sign up to set email alerts
|

Effects of modeling rote versus varied responses on response variability and skill acquisition during discrete‐trial instruction

Abstract: Despite its advantages, discrete-trial instruction (DTI) has been criticized for producing rote responding. Although there is little research supporting this claim, if true, this may be problematic given the propensity of children with autism to engage in restricted and repetitive behavior. One feature that is common in DTI that may contribute to rote responding is the prompting and reinforcement of one correct response per discriminative stimulus. To evaluate the potential negative effects of rote prompts on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Carroll and Kodak (2015) demonstrated slightly more variability during the acquisition of intraverbal categorization with a variable vocal model and instructive feedback compared to variable vocal models without instructive feedback. Peterson et al (2019) demonstrated initial variability during the acquisition of a similar skill with a variable vocal model relative to a rote vocal model. Both studies incorporated an adapted alternatingtreatment design, and, therefore, the results may be due partly to carryover effects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Carroll and Kodak (2015) demonstrated slightly more variability during the acquisition of intraverbal categorization with a variable vocal model and instructive feedback compared to variable vocal models without instructive feedback. Peterson et al (2019) demonstrated initial variability during the acquisition of a similar skill with a variable vocal model relative to a rote vocal model. Both studies incorporated an adapted alternatingtreatment design, and, therefore, the results may be due partly to carryover effects.…”
Section: Discussionmentioning
confidence: 99%
“…We are only aware of two published studies that demonstrated the efficacy of teaching strategies without a lag schedule of reinforcement on response variability for children with autism (Carroll & Kodak, 2015;Peterson et al, 2019). Carroll and Kodak (2015) demonstrated slightly more variability during the acquisition of intraverbal categorization with a variable vocal model and instructive feedback compared to variable vocal models without instructive feedback.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although children typically learn intraverbals incidentally (Hart & Risley, ); those diagnosed with an autism spectrum disorder (ASD) might require explicit training to do so (e.g., Allan, Vladescu, Kisamore, Reeve, & Sidener, ; DeSouza, Fisher, & Rodriguez, ; Dickes & Kodak, ; Eikeseth & Smith, ; Haggar, Ingvarsson, & Braun, ; Ingvarsson & Hollobaugh, 2011; Ingvarsson, Kramer, Carp, Petursdottir, & Macias, ; Ingvarsson & Le, ; Kisamore, Karsten, & Mann, ; Peterson, Rodriguez, & Pawich, ; Valentino, Shillingsburg, & Call ; Vedora, Meunier, & Mackay, ). The acquisition of intraverbals (i.e., answer questions, fill‐in the blanks, chain words together) is not only important for the development of a complex verbal repertoire (e.g., conversational skills), but it may create additional opportunities for contacting reinforcement through interactions with peers and adults (Ingvarsson, Tiger, Hanley, & Stephenson, ).…”
mentioning
confidence: 99%